2018
DOI: 10.1080/17460441.2018.1430763
|View full text |Cite
|
Sign up to set email alerts
|

Hot-spot analysis for drug discovery targeting protein-protein interactions

Abstract: Protein-protein interactions are important for biological processes and pathological situations, and are attractive targets for drug discovery. However, rational drug design targeting protein-protein interactions is still highly challenging. Hot-spot residues are seen as the best option to target such interactions, but their identification requires detailed structural and energetic characterization, which is only available for a tiny fraction of protein interactions. Areas covered: In this review, the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 119 publications
(135 reference statements)
0
61
0
Order By: Relevance
“…Protein-protein interactions (PPIs) are involved in the majority of diseases, and thus are essential to understand, prevent and correct pathological situations. Indeed, experimental studies show that many pathological mutations can affect protein-protein interactions, either by disrupting the entire interaction network of the mutated protein, or by specifically affecting some interactions [1] , [2] , [3] . In this context, PPIs emerge as attractive targets for drug discovery, and the field is shifting the focus of target identification and characterization from individual proteins to interaction networks [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein-protein interactions (PPIs) are involved in the majority of diseases, and thus are essential to understand, prevent and correct pathological situations. Indeed, experimental studies show that many pathological mutations can affect protein-protein interactions, either by disrupting the entire interaction network of the mutated protein, or by specifically affecting some interactions [1] , [2] , [3] . In this context, PPIs emerge as attractive targets for drug discovery, and the field is shifting the focus of target identification and characterization from individual proteins to interaction networks [4] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the path from a hit to a therapeutic drug is challenging. Indeed, few small-molecule PPI inhibitors have already been approved by FDA or are in clinical trials [2] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…3 Qualitative computational methods have emerged as useful to identify possible binding site and interaction "hot-spots". 10,11 Site nding methods such as FTMap 12 and SiteMap 13 can provide guidance for regions where small molecules may interact, but their power to discriminate true from false sites breaks down for less druggable sites. 14 Given the dynamic nature of protein-protein interactions, 15 it is perhaps not surprising that methodologies based on molecular simulation are proving useful.…”
Section: Introductionmentioning
confidence: 99%
“…Many protein‐protein interactions (PPIs) regulate the disease state; therefore targeting the PPIs is crucial for drug discovery . Usually, the PPI‐interacting surfaces are large, flat, and lack the deep and well‐defined binding cavities.…”
Section: Introductionmentioning
confidence: 99%
“…9,17,19,20 Many protein-protein interactions (PPIs) regulate the disease state; therefore targeting the PPIs is crucial for drug discovery. 12,14,[21][22][23][24] Usually, the PPI-interacting surfaces are large, flat, and lack the deep and well-defined binding cavities. However, mutational analyses of PPI interfaces revealed that the binding affinity is not evenly distributed across the binding interfaces, but instead contributed by the small patch of amino acid residues know as hot spot.…”
mentioning
confidence: 99%